2016
DOI: 10.1111/1753-0407.12376
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting multiple models of progression of β‐cell loss of function in type 1 diabetes: Significance for prevention and cure

Abstract: Type 1 diabetes (T1D) results from a chronic autoimmune process that leads to β-cell destruction and exogenous insulin dependence. The natural history of T1D proposed by Eisenbarth suggested six relatively independent stages over the course of the entire disease process, which was considered to be linear and chronic. Based on this classical theory, immunotherapies aim to prevent or reverse all these periods of β-cell loss. Over the past 30 years, much novel information about the pathogenesis of T1D proved that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
(150 reference statements)
1
6
0
Order By: Relevance
“…The high prevalence of detectable C-peptide in this cohort is consistent with most other recent studies [3, 4] that have used highly sensitive assays. Of the 585 patients aged less than 15 years at onset and with at least 35 years duration, 85% had no C-peptide detectable with this assay.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high prevalence of detectable C-peptide in this cohort is consistent with most other recent studies [3, 4] that have used highly sensitive assays. Of the 585 patients aged less than 15 years at onset and with at least 35 years duration, 85% had no C-peptide detectable with this assay.…”
Section: Discussionsupporting
confidence: 91%
“…Studies using sensitive assays for C-peptide have shown that some degree of residual insulin secretion commonly persists for more than 5 years after diagnosis of type 1 diabetes [14]. However, few studies have examined the frequency with which C-peptide secretion persists after long duration of type 1 diabetes or across a wide range of ages of onset.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) is considered to result from a T‐cell‐mediated, irreversible, autoimmune destruction of insulin‐producing β cells, and patients inevitably develop exogenous insulin dependence . Although endogenous insulin secretion is usually overlooked in T1DM, residual islet β cell function does play important roles in achieving good glycemic control and reducing the risk of related chronic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, we have witnessed a plethora of developments in T1DM therapies that include insulin replacement, immunosuppression, antigen‐specific and cell‐based approaches. T1DM prevention in high‐risk individuals remains the highest priority where the goal is to maintain endogenous beta cell function (Creusot et al, ; Li et al, ). Therefore, protection of beta cells from cell death is considered as a new therapeutic target (Srimal and Dhawan, ; Ardestani and Maedler, ; Imai et al, ; Roy et al, ), where natural and safe anti‐inflammatory agents, such as curcumin (CUR)(Srimal and Dhawan, ; Castro et al, ), can perform better than some of the biological agents, such as canakinumab, a fully human anti‐IL‐1β monoclonal antibody (IgG‐1κ class), tested in trials with limited success (Cabrera et al, ).…”
Section: Introductionmentioning
confidence: 99%